Multi-criteria decision making in CBN grinding tool steel using TOPSIS method - Bui Thanh Danh; Vu Van Khoa; Nguyen Hong Linh; Hoang Xuan Tu; Nguyen Van Tung; Bui Thanh Hien (Journal of Military Science and Technology, 2023)
This paper introduces the results of a multi-criteria decision making (MCDM) study when CBN grinding SKD11 tool steel in a CNC milling machine. In this work, the TOPSIS method was applied to solve the MCDM problem, and the Entropy method was used to find the weight of criteria. Also, two criteria were chosen: surface roughness (SR) and material removal speed (MRS). Furthermore, an experiment with design L18 (61+33) was carried out using the Taguchi method. In the experiment, four input parameters were investigated: the dressing cut depth aed (mm), the wheel speed Rpm (rpm), the feed rate Fe (mm/min), and the wheel diameter d (mm). From the results of this work, the best experimental setup was proposed.